FOXP1 inhibits high glucose-induced ECM accumulation and oxidative stress in mesangial cells. (1st November 2019) - Xiang, Heli; Xue, Wujun; Wu, Xiaoyan; Zheng, Jin; Ding, Chenguang; Li, Yang; Dou, Meng
Abstract: Diabetic nephropathy (DN) is a common complication of diabetes that remains the major cause of end‐stage renal disease (ESRD). Forkhead box P1 (FOXP1) is a member of FOX family involved in the progression of diabetes. However, the pathogenic role of FOXP1 in DN remains unclear. This study was aimed to explore the effects of FOXP1 on glomerular mesangial cells (MCs) in response to high glucose (HG) stimulation. We found that HG stimulation markedly inhibited the FOXP1 expression in MCs in dose-and time-dependent manner. CCK-8 assay proved that FOXP1 overexpression attenuated HG-induced cell proliferation in MCs. FOXP1 exhibited anti-oxidative activity in HG-induced MCs, as proved by the decreased production of ROS and expressions of ROS producing enzymes, NADPH oxidase (NOX) 2 and NOX4. Besides, FOXP1 suppressed the expression and secretion of extracellular matrix (ECM) proteins including collagen IV (Col IV) and fibronectin (FN). Furthermore, FOXP1 overexpression significantly prevented HG-induced activation of Akt/mTOR signaling in MCs, and Akt activator blocked FOXP1-mediated cell proliferation, ROS production and ECM accumulation in MCs. Collectively, FOXP1 prevented HG-induced proliferation, oxidative stress, and ECM accumulation in MCs via inhibiting the activation of Akt/mTOR signaling pathway. The findings suggested that FOXP1 might be a therapeutic target for the treatment of DN. Highlights: Expression of FOXP1 in MCs under HG condition. FOXP1 inhibits ROS level and NOX2/4 expression in MCs induced by HG. FOXP1 reduces the expression of FN and Col IV in MCs induced by HG. FOXP1 suppresses the activation of Akt/mTOR pathway in HG-stimulated MCs.